Biochemical alterations in kidneys of infant and adult male rats due to exposure to the neonicotinoid insecticides imidacloprid and clothianidin - Ozsahin, Ayse Dilek; Bal, Ramazan; Yilmaz, Okkes (Royal Soc Chemistry, 2014)
Imidacloprid (IMI) and clothianidin (CTD) are the most important of the neonicotinoid insecticides known to target the nicotinic acetylcholine receptor (nAChR) in insects and, potentially, in mammals. In the present study, we aimed to investigate if daily oral administration of IMI and CTD at low subchronic doses for 90 days has any deleterious effects on the biochemical parameters of infant and adult male rats. Animals were randomly divided into five groups of seven rats each: controls, IMI-infant and IMI-adult treatments at 4 mg per kg BW per day, and CTD-infant and CTD-adult treatments at 12 mg per kg BW per day by oral gavage. Kidneys of rats exposed to IMI and CTD showed biochemical changes. Based on the biochemical studies it is evident that IMI and CTD produce significant effects in male rats at 4 and 12 mg per kg per day of exposure. In conclusion, the present animal experiments revealed that the treatment with IMI and CTD at NOAEL (no observed adverse effect level) dose-levels causes changes in kidney biochemical parameters which seem to be dependent on the pesticide and age of the animal (infant or adult).
Keywords: Nicotinic Acetylcholine-Receptors; Central-Nervous-System; Oxidative Stress; Arachidonic-Acid; Toxicity; Quantification; Cholesterol; Growth; Liver